Creating E-learning for English Vocabulary Enrichment for Junior High School Students - Rafidah Eltalitha Salas (UPT P2M Politeknik Negeri Malang, 2026)
The limited enrichment of students’ vocabulary was because of the use of traditional lecture methods in schools. This method often leads to low student enthusiasm and interest in English lessons, which in turn hinders vocabulary development. This research aims to develop an e-learning platform to improve students’ English skills through vocabulary enrichment. Using the Design, Development, Research (DDR) model by Richey and Klein, data were collected through interviews, observations, and questionnaires. The findings showed a strong need from students that e-learning can be an alternative to digital learning, especially for vocabulary development. The researcher adjusted the design of the platform based on students’ needs and feedback obtained during interviews. During the validation and implementation stages, the e-learning platform proved to be workable and useful as an additional learning medium. The final product of this research is a website-based digital learning platform that comprises two main components: materials and quizzes. The platform provides an effective solution to support vocabulary enrichment for students who have limited English vocabulary.